2022
DOI: 10.3389/fvets.2022.834031
|View full text |Cite
|
Sign up to set email alerts
|

Canine Vaginal Cytology: A Revised Definition of Exfoliated Vaginal Cells

Abstract: Vaginal cytology is an important examination method in the context of gynecological disorders and cycle staging in the bitch. While collection and preparation of samples are easy, the evaluation appears to be challenging. Inconsistent definitions of cell attributes such as size, cornification and the appearance of the nucleus have been published. The aim of the project was to develop a tutorial for vaginal cell determination. To get a deeper insight into the use of cytology in practice, an online survey was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This phenomenon has also been observed in felines where the percentage of surface cells increases slightly during the follicular phase when the transition from estrus to post-estrus occurs [ 48 ]. This exfoliation process is an indicator of cell necrosis that occurs during the period of transition from round cells (basal and parabasal) to irregular cells, whose nuclei progressively decrease in size [ 49 , 50 ]. The dimensions observed in parabasal and intermediate cells are similar to those reported in other species and even in other camelid species such as the alpaca [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has also been observed in felines where the percentage of surface cells increases slightly during the follicular phase when the transition from estrus to post-estrus occurs [ 48 ]. This exfoliation process is an indicator of cell necrosis that occurs during the period of transition from round cells (basal and parabasal) to irregular cells, whose nuclei progressively decrease in size [ 49 , 50 ]. The dimensions observed in parabasal and intermediate cells are similar to those reported in other species and even in other camelid species such as the alpaca [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, such discrepancies may be attributed to the differences in the period of observation of the vaginal smears; or variability in reporting of different cell types and/or the technical experience in interpretation of the vaginal smears (Moxon et al, 2010;Arlt, 2018), since the exfoliated cells once removed from their natural environment may assume forms differing from similar cells as they appear in sec-tions; and therefore, change shape and structure and may become dehydrated. Some authors (Ducatman and Wang, 2002;Reckers et al, 2022), have also noted that the cellular picture as revealed by vaginal smear was never exactly the same in any two oestrus cycles.…”
Section: Vaginal Exfoliative Cytologymentioning
confidence: 99%
“…It is generally accepted that exfoliated cell types in the vaginal smear are related to the stage of the estrous cycle (Cora et al, 2015); which makes the vaginal exfoliative cytology, a simple, non-invasive technique routinely employed by clinicians for reproductive diagnostics (Moxon et al, 2010;Zohara et al, 2014;Sharma and Sharma, 2016;Siregar et al, 2016;Antonov, 2017;Sitaresmi et al, 2018;Reckers et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The results of gynecological examinations are very important in supporting breeding management. Furthermore, a vaginal smear examination is a standard gynecological examination because it allows insight into the potential effect of estrogen and vaginal health status (Reckers et al, 2022) [4] . Examination of vaginal cytology may provide valuable information about the stage of the ovarian cycle.…”
Section: Introductionmentioning
confidence: 99%